The art of international negotiation - Posses, Frederick (London : Business Books, 1978)
Economic reality consists of indefatigable cut throat competition, tariffs are obstructive, money is dear, labour is intransigent, inefficient and indifferent to the consequences of its self concern.
aia 03/07/17
Loans
Keywords: International business enterprises; International business enterprises -- Law and legislation; Commercial law; Negotiation in business; Companies Foreign trade Negotiations; International business enterprises--Law and legislation; Commercial law; Negotiation in business